THE CONCEPT AND LEVELS OF MAHASANTRI UNDERSTANDING ON RELIGIOUS MODERATION IN MA'HAD AL-JĀMI'AH UIN ANTASARI BANJARMASIN - Riza Saputra (UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
The study of religious moderation seems to be a wave today. In the framework of higher education, although studies on religious moderation have been widely carried out in the last few decades, studies on religious moderation are still limited to the program activities, roles, and efforts made by PTKIN. This study wants to know the success of these programs and efforts by looking at the level of understanding of Ma'had al-Jāmi’ah UIN Antasari students in describing religious moderation. This study aimed to determine the understanding of Mahasantri and the factors influencing their knowledge of religious moderation. This qualitative descriptive field study shows the results that mahasantri's understanding of religious moderation can be categorized into several key concepts; religious moderation is: 1) the Middle Way, fair and balanced; 2) it is not rigid and fanaticism in religion; 3) it is the one that is not exaggerating, 4) it does not impose its beliefs on others, 5) Religious Moderation is a Process and Tolerance is a result of it. At the level of understanding, mahasantri’s understanding is not only at the first level of understanding (translation), but their understanding has also entered the second and third levels of understanding, namely interpretation, and extrapolation.